Chemical Fixation of \(CO_2\) Using NaOH and \(CaCl_2\): An Innovative Approach for \(CO_2\) Capture - Kenji Sorimachi (Recent Developments in Chemistry and Biochemistry Research Vol. 6, 2024)
Carbon dioxide (CO2) emissions pose a significant challenge for climate change mitigation. This study addresses the need for effective CO2 capture methods by introducing an innovative approach utilizing NaOH and CaCl2 for CO2 fixation. The objective was to develop a cost-effective and practical solution for capturing CO2 from industrial and atmospheric sources. The experimental results demonstrated that this method effectively captures and converts CO2 into CaCO3, a stable and environmentally benign compound. The process was shown to be efficient in various conditions, including high CO2 concentrations. The findings suggest that this approach could be integrated into existing systems to enhance CO2 capture and contribute to climate change mitigation strategies.